Landscape Design to Improve the Tourism Quality As the Part of Riverside Settlement’s Revitalization - Minggra, Restu; ., Firmansyah; Heri Sofian, Dian (KnE Social Sciences, 2019)
This research of riverside settlement in Kampung Beting extends our understanding of Kapuas riverside as a place to live and make a living. Kampung Beting set on the delta of Kapuas river branching and put it in the history as the part of Pontianak urban city developments. This research explores the phenomenon of the residents that live above the water can adapt and use the Kapuas River as their place to grow and cultivate their domestic productions. The finding shows that there are no specific programs from the residents and also from the government to improve the quality of the domestic output, so the home-based business (hydroculture) are poorly handled. Connected floating corridors, the genuine of water culture, and riverside picturesque are several of the potential factors that can be improved to transform Kampung Beting into an attractive tourist area. The study suggests the landscape design of river aquaculture that can escalate the variation of the venture, increase the resident’s productivity, and create a conducive environment for stability. Designing tourist routes within Kampung Beting, not only introduces cultural and historical values but also aims to increase income for the community.